Implicações da disponibilidade de espaço no confinamento de bovinos de corte - Macitelli Benez, Fernanda [UNESP] (2015)
The objective of this research was to evaluate the implications of the space availability in feedlot beef cattle on animal welfare, performance and carcass and meat quality. One thousand, three hundred and fifty bulls were confined within three space allowance: 6 (T6), 12 (T12) and 24 (T24) m2/animal. All animals received the same diet. The animal welfare were assessed using environmental (dust score and mud depth) and animal based indicators, part of these measurements was carried out with the animals housed in confinement pens by using behavioral (number of animals standing, lying down, or in the feed bunk), comfort (percentage of dirty animals), and health indicators (number of coughs and sneezes per minute, and the percentages of animals with diarrhea, hooves alterations, locomotion problems, tegument alterations, and nasal and ocular discharges), and part after slaughtering the animals, evaluating health indicators, with macroscopic diagnosis of animal viscera (percentage of animals with bronchitis, emphysema, nephritis and urinary cyst), and stress indicators besides the collection of the left and right adrenal glands from 20% of the animals from each treatment (to assess the weight and cortical and medullar areas). Growth performance (final body weight, average daily gain weight, hot carcass weight), and carcasses (number and severity of bruises and degree of fat finishing), and meat quality (pH) indicators were also measured. In general, the results showed that the T24 offered better environmental conditions for the finishing phase of beef cattle than the other treatments, evidenced by the lower frequency of occurrence of dust and mud depth (P < 0.01), lower percentages of animals with nasal and ocular discharges and locomotion problems (P < 0.05), and lower percentage of animals diagnosed with bronchitis, emphysema, nephritis and urinary cyst. In addition, T24 showed higher mean of daily weight gain (P < 0.01), lower means ...